The Impact The Impact of BOPO, ROE and NIM on Corporate Value: An Empirical of Banking Sector in LQ45 Stock: The Impact of BOPO, ROE and NIM on Corporate Value - Tahmat Tahmat; Yayan Cahyana; Emmilya Sabrina Pratiwi (International Journal of Islamic Business and Management Review, 2023)
The purpose of this study is to determine how the development of Operating Expenses to Operating Income, Return On Equity, Net Interest Margin and Price Earning Ratio and how the variable effect of Operating Expenses on Operating Income, Return On Equity, and Net Interest Margin partially and simultaneously on the Company Value proxied by PER ( Price Earning Ratio). The method used in this research is descriptive quantitative with multiple linear regression analysis. The results showed that the variables Operating Expenses to Operating Income, Return On Equity partially had a significant effect, and the Net Interest Margin variables partially did not have a significant effect on the Price Earning Ratio. Variable Operating Expenses to Operating Income, Return On Equity, Net Interest Margin simultaneously have a significant effect on the Price Earning Ratio.